Evaluation of neurobiological and antioxidant effects of novel melatonin analogs in mice - Jana Tchekalarova; Natasha Ivanova; Zlatina Nenchovska; Rumiana Tzoneva; Tzveta Stoyanova; Veselina Uzunova; Slavina Surcheva; Alex Tzonev; Violina T. Angelova; Pavlina Andreeva-Gateva (Elsevier, 2020)
Based on the pharmacophore model of melatonin (MT1) receptor, we recently synthesized a series of indole derivatives that showed anticonvulsant activity with low neurotoxicity and hepatotoxicity in rodents. In the present study, the three most potent C3-modified derivatives with hydrazine structure 3c, 3e, and 3f, with 2-chlorophenyl, 2-furyl, and 2-thienyl fragments, respectively, were selected, and their neurobiological activity was explored in mice. In Experiment #1, the dose-dependent anxiolytic effect of a single i.p. administration of the novel compounds at doses of 10, 30, and 60 mg/kg were studied in the open field (OF) test. In Experiment#2, the analgesic effect of 3c, 3e, and 3f (30-100 mg/kg) was tested in the hot plate test and formalin test. Experiment#3 was designed to assess the antidepressant-like activity of 3c, 3e, and 3f (10-60 mg/kg). The forced swimming test (FST) and tail suspension test (TST)-induced effect on markers of oxidative stress in the frontal cortex (FC), and the hippocampus was evaluated. Melatonin was used in the same doses as melatonin analogs in all three experiments as a positive control. Desipramine (10 mg/kg) was also applied as a control in the FST. The three melatonin analogs bearing hydrazide/hydrazone substitution at 3C of the indol scaffold demonstrated improved antidepressant-like activity compared to the melatonin. The tested substances are devoided of anxiolytic effects. The antioxidant activity of the melatonin analogs and analgesic potential is comparable to that of melatonin. The 3C substitution with hydrazide/hydrazone moiety substantially contributes to the antidepressant and antioxidant activity of the melatonin analogs.